A inserção da mulher europeia na conquista do “Novo Mundo” – perspectivas literárias - Uber, Beatrice (2017)
Since the beginning of the records about Americas’ colonization, the woman had been considered inferior and submissive to men by the European phallocentric and Jewish-Christian point of view present in the historiographic discourse that determined the official version of this past. However, she was essential to assure the colonists’ stay in the land to be pioneered. Many of the settlers had the feminine presence as an anchor to strengthen their stay in the “New World”. After the wedding ceremony, the woman was responsible for taking care of the house, being a good wife and an excellent mother, according to the ideology imposed by Church, which corroborated the patriarchal vision of the colonizing metropolis prevailing that time. Starting from this historical situation, the present research proposes reflexions and analyses about the insertion theme of the white European woman in the “New World”. Our purpose is to present, throughout an analysis of the books Desmundo (1996), by Ana Miranda, and Bride of New France (2013), by Suzanne Desrochers, how each one builds a symbolic representation of this process of displacement, strangeness and adaptation to a new reality of the white European woman in the beginning of the Brazilian colonization period, in the sixteenth century, and of the Canadian, in the seventeenth century, respectively, under the auspices of the historical novel. We also aim to analyze if the leading characters, Oribela de Mendo Curvo and Laure Beauséjour, keep their received instruction by the institutions that housed them or if their conceptions change when they start living in the “New World”, and to verify the confrontation of these literary visions with the official discourse. Based on this, we aim to show how the voices of the “orphans of the queen”, from Portugal, and the “king’s daughters”, from France, reflected in the literary discourse, can differ from the historiographic discourse and reveal new perspectives from this past. The research we did was supported by Comparative Literature. Authors like Afonso Costa (1946), Rodolfo Garcia (1946), Jim Sharpe (1992), Gilmei Francisco Fleck (2007, 2011, 2014, 2017), Aimie K. Runyan (2010), and Marcia A. Zug (2016) are used as theoretical support for the historical contextualization of the facts reread by fiction, and to establish the specific modalities of the historical novel in which the corpus is inserted. As a result of this investigational procedure, this research sheds light on the historical vision about the white European woman insertion in our continent. When highlighting the woman’s participation in this historical process, we observed the hybrid narratives of history and fiction update the theme and present a critical rereading of the events in relation to the happenings of the past perpetrated by the writing of historiography.